First study of vitellogenesis of the broad fish tapeworm Diphyllobothrium latum (Cestoda, Diphyllobothriidea), a human parasite with extreme fecundity - Yoneva, Aneta; Kuchta, Roman; Scholz, Tomáš (Parasitology international, 2014)
In the present study, the process of vitellogenesis of one of the most prolific organisms, the broad tapeworm, Diphyllobothrium latum, the causative agent of human diphyllobothriosis, was studied for the first time using transmission electron microscopy. Cytochemical staining with periodic acid-thiosemicarbazide-silver proteinate for detection of glycogen was applied. Starting from the periphery toward the center of the vitelline follicle four stages of vitellocytes are differentiated: immature vitellocytes, early maturing vitellocytes, advanced maturing and mature vitellocytes. Differentiation into mature vitellocytes involves the formation of shell globule clusters containing shell globules, large amount of saturated lipid droplets and glycogen. A peculiar ultrastructural feature of D. latum vitellogenesis is the presence of lamellar bodies in the cytoplasm of mature vitellocytes. This feature is similar to that present in the closely related caryophyllideans and spathebothriideans. Despite the great similarity observed in the embryonic development of diphylobothriideans, caryophyllideans and spathebothriideans, and the fact that their vitellocytes share a feature not reported from other cestode groups, there are substantial differences in the morphology of vitelline clusters, types, amount and localization of their nutritive reserves.
Keywords: Animals; lidé; vitelogeneze; fertilita; zvířata; Female; Fertility; Vitellogenesis; difylobotriáza; Diphyllobothrium; Diphyllobothriasis; ženské pohlaví; Humans